ANGGAWASTA: KESADARAN JIWA DALAM KEKAWIN DHARMA NISKALA - Dwijayanthi, Ni Made Ari; Widiantana, I Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
Anggawasta (Author), the Universe, and the Creator are the author's methods in Kekawin Dharma Niskala to get unification with the universe through his work. Anggawasta is the term to use represent author in the Kekawin Dharma Niskala. The focus of this research is to reveal the form, function, meaning, and position of the author in text. Pierce's semiotic theory is used to interpret the signs in the kekawin.